2006
DOI: 10.1248/cpb.54.982
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Holothuroidea, 17. Isolation and Structure of Biologically Active Monosialo-Gangliosides from the Sea Cucumber Cucumaria echinata

Abstract: Three new monosialo-gangliosides, CEG-3 (3), CEG-4 (4), and CEG-5 (5), were obtained, together with two known gangliosides, SJG-1 (1) and CG-1 (2), from the lipid fraction of the chloroform/methanol extract of the sea cucumber Cucumaria echinata. The structures of the new gangliosides were determined on the basis of chemical and spectroscopic evidence to be 1-O-[4-O-acetyl-alpha-L-fucopyranosyl-(1-->11)-(N-glycolyl-alpha-D-neuraminosyl)-(2-->6)-beta-D-glucopyranosyl]-ceramide (3) and 1-O-[alpha-L-fucopyranosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Continuing the previous studies, three cerebroside molecular species (BAC-1, BAC-2 and BAC-3) was obtained from the less polar lipid fraction of CHCl 3 /MeOH extract of sea cucumber Bohadschia argus (Janomenamako in Japanese). The structures of BAC-1, BAC-2 and BAC-3 could be determined by hitherto reported chemical and spectroscopic methods 2,4,5) as the molecular species of typical types of glucocerebrosides, 2,4,5) namely, a sphingosine-type b-glucocerebroside possessing non-hydroxy fatty acid (BAC-1), a sphingosine-type b-glucocerebroside possessing 2-hydroxy fatty acid (BAC-2), and phytosphingosine-type b-glucocerebroside possessing 2-hydroxy fatty acid (BAC-3), respectively (data not shown), as revealed in Fig.…”
mentioning
confidence: 84%
“…[1][2][3][4][5][6][7] Continuing the previous studies, three cerebroside molecular species (BAC-1, BAC-2 and BAC-3) was obtained from the less polar lipid fraction of CHCl 3 /MeOH extract of sea cucumber Bohadschia argus (Janomenamako in Japanese). The structures of BAC-1, BAC-2 and BAC-3 could be determined by hitherto reported chemical and spectroscopic methods 2,4,5) as the molecular species of typical types of glucocerebrosides, 2,4,5) namely, a sphingosine-type b-glucocerebroside possessing non-hydroxy fatty acid (BAC-1), a sphingosine-type b-glucocerebroside possessing 2-hydroxy fatty acid (BAC-2), and phytosphingosine-type b-glucocerebroside possessing 2-hydroxy fatty acid (BAC-3), respectively (data not shown), as revealed in Fig.…”
mentioning
confidence: 84%
“…1 H-and 13 C-NMR spectra were recorded on a Jeol GX-270 spectrometer (270, 67.8 MHz) or a Varian Unity-500 spectrometer (500, 125 MHz). Negative-ion FAB-MS spectra were acquired with a Jeol JMS-SX-102 mass spectrometer (xenon atom beam; matrix, triethanolamine).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] In the study of the GSLs of the sea cucumber Cucumaria echinata (gumi in Japanese), we reported the isolation and structure of glucocerebrosides 2,4) and monosialogangliosides.1) In a continuation of the preceding studies, 1) the further isolation and characterization of the more polar biologically active gangliosides from the sea cucumber C. echinata were carried out to develop novel medicinal resources from natural marine products. In this paper, we report the isolation and characterization of three new disialoand trisialo-gangliosides from the whole bodies of C. echinata.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We attempted to determine the absolute configuration (D or L) of the sialic acid residues in the gangliosides 3,4) from the sea cucumber Cucumaria echinata.…”
mentioning
confidence: 99%